Dmitry Bortniansky. Choral Concert № 34 (Some Performing and Conductor’s Problems) - Ihor Tsmur (Pedagogical Discourse, 2013)
Basic trends of formation of creative personality of D.Bortnyansky – master of choral music, composer of the end of the XVIII – beginning of the XIX century are studied in the article, the generalization of the definite theoretical material connected with the choral creative work of the composer, as well as the relation with conducting-choral preparation of the future musicians-pedagogues is offered. Conducting-choral analysis of the «Choral Concert № 34» is offered  some performing and conducting problems upon which it can be concluded about the relevance and necessity of the using of this creative work in modern conductor-choral practice are studied.